Study of land potential based on soil characteristics using interpolation and scoring methods for non agricultural uses: a case study in Wonosalam, Jombang District, East Java - Siswanto, Siswanto; Sasongko, Purnomo Edi (Agrovigor, 2024)
The state asset land managed by UPN "Veteran" East Java is located in the Wonosalam District based on land certificate data issued by the Jombang BPN covering 13.5 hectares. Currently more than 50% of the land has not been used optimally to support learning, research and community service. The problems that arise in utilizing land assets to support learning, research and community service are 1) the legal boundaries of land ownership are not yet clear, 2) there is no land use master plan to support the learning process, 3) there is no potential data that can be used. prepare use and development plans. Against the background of the problems above, this research aims to map the potential of state land assets by "spatial interpolation, scoring and weight overlay" of land characteristics. Interpolation is a way of calculating the area of several representative measurement points, while scoring and "Weight Overlay" is a facility provided by ArcMap GIS which combines input spatial data with weighting (weight factor) and scoring. Land unit maps are obtained from overlaying relief, geology, slope and land use maps. Interpolation, Scoring and Weight Overlay of the nine land characteristics yielded a potential land asset for buildings, good category 16.61% (44,130.38 m2); moderate 25.66% (67,382.75 m2) and bad 7.523% (19,784.88 m2). Playing field potential, good category 54.73% (71,865.05 m2) and medium 45.27% (59,432.62 m2). Potential for road infrastructure development in the good category 32.38% (42513.74 m2); Moderate 42.68% (56035.24 m2) and Bad 24.94% (32748.69 m2), and all of these potentials are in Slightly Flat topography (Slope, 0-3%) to hilly (Slope, 15-25%).